Internal Audit Effectiveness Antecedents In Higher Education: Do Competency And Time Budget Pressure Matter? - Turnanto, Agus; Muhammad, Erfan; Hakim, Tito IM. Rahman (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
Internal control plays an important role in increasing accountability and operational efficiency in higher education institutions. This study aims to prove the effect of competency, independence, and time budget pressure on the effectiveness of internal audits. The sampling technique for this research was snowball sampling of lecturers who were internal supervisory unit members at universities in East Java. The samples obtained were from 60 respondents. Data analysis technique using smartPLS. The results of this study indicate that competency and time budget pressure have a significant effect on internal audit effectiveness, while independence has no significant effect on internal audit effectiveness. The rectorate is expected to be able to provide an additional budget for internal supervisory unit members to attend training in order to improve their competency. The rectorate also ordered internal supervisory unit members to work on audit assignments more quickly and efficiently.